MODAL SOSIAL PEMANTIK UNTUK KOTA KREATIF - Tubagus Arya Abdurachman (Jurnal Renaissance, 2018)
The discussion of this research is the development of creative cities in a country is the result of the efforts of the government and creative actors in the city in the country. Creative city can not be separated from the potential of social capital that is owned by the people in the city. Social capital is a social organization concept that includes network of norms and social trusts that facilitate mutual coordination and cooperation including in developing the regional economy. This research aims to (1) know the contribution of social capital in making a creative city, (2) express the social capital and creativity of individuals and communities to realize creative city, and (3) know aspects of social capital that dominant influence on a creativity of the city. The method of this research is qualitative primary data with technic observation and indepth interview, also secondary data in the form of document and archive analysis from Bandung city as one of creative city in Indonesia. Research is done during 2015-2016. Conclusions this research are (1)Social capital that form trust, tolerance, cooperation, openness, and independence of the community greatly contributes in the creation of creative city because through the braided integration of social capital that forms a norm of behavior binding for its citizens to be creative and does not require material capital,(2)Individual urban creativity formed through the process of socialization of elements of social capital in the life of society to trigger creativity of individuals and society as a whole, and (3) The form of openness, tolerance, and cooperation are the dominant elements of social capital in growing the creativity of individuals and societyKeywords: Creatif city, Social capital